History of formation of positive psychotherapy, as a direction of psychology (second half of XX – early XXI centuries) - O. M. Sirenko (History of science and technology, 2018)
For the modern historical science, the actual task is to study the history of the becoming of new directions of social and humanitarian sciences, in particular in the field of psychology. The article is devoted to the analysis and systematization of the main events that led to the constitution of positive psychotherapy in an independent direction of modern psychology. Methodological basis of the work are methods of classification and systematization of sources, which allowed to generalize and systematize the main views on the role and place of positive psychotherapy in psychological science, as well as chronological, typological, comparative methods of historical knowledge, which allowed to distinguish the main stages of the development of positive psychotherapy on the path from the author psychotherapeutic method Nossrat Peseschkianto an independent direction of psychology. The analysis of the sources allowed us to give an objective assessment of Nosrat Peseschkian's activity of the German neurologist, psychiatrist and psychotherapist of Iranian origin as the founder of the method of positive therapy and its contribution to the dissemination and popularization of the method. It has been established that thanks to the personal contribution of Nosrat Peseschkian, positive psychotherapy has been recognized by scholars as a separate line of psychology, and it has many followers among practicing psychologists and psychotherapists. Among other areas, positive psychotherapy is positioned as humanistic transcultural psychodynamic therapy, which is based on the positive concept of human nature. It is founded on three main principles: hope, balance, and counseling, and is a conflict-centered, integrative short-term therapy that allows you to address the psychological problems of an individual taking into account the cultural characteristics of patients. At the present stage of development, psychology as a science is characterized by the active integration of psychological theories into psychotherapeutic and counseling practice. Positive psychotherapy should be regarded as an illustrative example of the effectiveness of this trend, and therefore the study of the main stages of the formation of the method and its institutionalization as an independent direction of psychological science is the purpose of this work.